2004
DOI: 10.1136/adc.2003.037531
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation for gastroenteritis in Western Australia

Abstract: Aims: To document gastroenteritis hospitalisations of the 1995-96 cohort of infants born in Western Australia to mid-2002, and to assess factors associated with their hospitalisations and readmissions. Methods: Retrospective analysis of the State's hospitalisation data, Midwives' Notification of Births data, the Australian Bureau of Statistics mortality data and clinical and demographic information. Results: Aboriginal infants were hospitalised for gastroenteritis eight times more frequently than their nonAbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Respiratory and infectious conditions were the most common reasons for avoidable hospitalization among all children in the cohort, with Aboriginal children more likely to be admitted for all conditions. These findings are consistent with other Australian data on common conditions resulting in pediatric emergency department presentations [ 34 ] and higher hospitalization rates for respiratory diseases [ 35 39 ] and gastroenteritis [ 38 , 40 42 ] among Aboriginal children in Western Australia. Although we were unable to ascertain the burden of these conditions outside of the hospital setting, other studies have previously reported a high burden of respiratory diseases [ 43 – 46 ], skin infections [ 47 ] and otitis media [ 48 50 ] in Aboriginal children, particularly in remote communities.…”
Section: Discussionsupporting
confidence: 91%
“…Respiratory and infectious conditions were the most common reasons for avoidable hospitalization among all children in the cohort, with Aboriginal children more likely to be admitted for all conditions. These findings are consistent with other Australian data on common conditions resulting in pediatric emergency department presentations [ 34 ] and higher hospitalization rates for respiratory diseases [ 35 39 ] and gastroenteritis [ 38 , 40 42 ] among Aboriginal children in Western Australia. Although we were unable to ascertain the burden of these conditions outside of the hospital setting, other studies have previously reported a high burden of respiratory diseases [ 43 – 46 ], skin infections [ 47 ] and otitis media [ 48 50 ] in Aboriginal children, particularly in remote communities.…”
Section: Discussionsupporting
confidence: 91%
“…Significant differences in PAHs among a particular racial or insurance subgroup could indicate differences in the use of ambulatory care in community settings and provide insights into opportunities for improving the quality of primary care. 2,[17][18][19][20][21][22] …”
mentioning
confidence: 99%
“…Admission rates for gastroenteritis in Australia are nearly seven times higher in Indigenous communities than in non‐Indigenous communities. Rates are also higher in regional and remote areas than in urban settings 5 . Our own analysis of hospital separation data from Queensland's northern zone for 1996–2001 shows an age‐standardised hospital separation rate for gastrointestinal infection 2.32 times higher for Indigenous patients than non‐Indigenous patients (95% CI, 2.17–2.48).…”
mentioning
confidence: 85%